2006
DOI: 10.1038/sj.sc.3101915
|View full text |Cite
|
Sign up to set email alerts
|

Physical capacity in wheelchair-dependent persons with a spinal cord injury: a critical review of the literature

Abstract: Study design: Review of publications. Objective: To assess the level of physical capacity (peak oxygen uptake, peak power output, muscle strength of the upper extremity and respiratory function) in wheelchair-dependent persons with a spinal cord injury (SCI). Setting: Erasmus MC, University Medical Centre Rotterdam, The Netherlands. Methods: Pubmed (Medline) search of publications from 1980 onwards. Studies were systematically assessed. Weighted means were calculated for baseline values. Results: In tetraplegi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
114
2
14

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(136 citation statements)
references
References 76 publications
6
114
2
14
Order By: Relevance
“…As expected, the multivariate models showed that level of lesion and sex were important predictors of physical capacity. 14,23,26,40 These models also identified other predictors, however, which made small but significant contributions to the explained variance, some of which are modifiable.…”
Section: Prognostic Models For Different Aspects Of Physical Capacitymentioning
confidence: 98%
See 3 more Smart Citations
“…As expected, the multivariate models showed that level of lesion and sex were important predictors of physical capacity. 14,23,26,40 These models also identified other predictors, however, which made small but significant contributions to the explained variance, some of which are modifiable.…”
Section: Prognostic Models For Different Aspects Of Physical Capacitymentioning
confidence: 98%
“…Furthermore, the prognostic models that were developed had different shortcomings. 13,14 First, the outcome measure may have been limited by a ceiling effect, which would hamper the prediction of outcome at a later phase of recovery. 2,4,14 Second, often only 1 component of physical capacity was investigated, whereas the simultaneous assessment of different aspects (eg, endurance capacity, muscle strength, respiratory function) may more specifically indicate the required treatment strategy.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, inter-subject variability in body anthropometrics was not considered, with the musculoskeletal model representing a 50th percentile able-bodied male. However, the physical capacity of wheelchair users varies with age, gender and nature of impairment and is generally less than that of nonwheelchair users (e.g., Janssen et al, 2002;Haisma et al, 2006). Future work should include the development of subject-specific models (e.g., Zajac et al, 2002;Fregly et al, 2012) to help determine the optimal seat position for individual users.…”
Section: Limitations and Future Workmentioning
confidence: 99%